Histopathological Study of Lower Gastrointestinal Tract Biopsies in 600 Cases - Jasmin Haridas Jasani; Shivani Bhaveshbhai Vora; Nidhi Amrutlal Patel (Journal of Clinical and Diagnostic Research, 2021)
Introduction: Broadly the whole gastrointestinal tract can be divided into upper and lower segments by taking the insertion of ligament of Treitz as a landmark. The disorders of Lower Gastrointestinal Tract (LGIT) are responsible for a great number of morbidity. The microscopic analysis and the determination of histological types are thus helpful in deciding treatment options, predicting prognosis and conducting epidemiological studies and research. Delay in diagnosis causes direct as well as distant metastasis leading to advanced stage of the disease. Aim: To emphasise the usefulness of LGIT biopsy in diagnosing the conditions, thus helping the surgeons to decide further management prior to resection, especially in malignant cases. Materials and Methods: An observational retrospective study of various LGIT biopsies was done at Pathology Department of Sumandeep Vidyapeeth, Vadodara, Gujarat, India. The study was based on the HPE of lesions received in the duration from June 2019 to September 2020. In this study, the records of LGIT specimens including small intestine, large intestine, rectum and anus were included. Due importance was paid to brief clinical history with patient’s age, inpatient number and presenting signs and symptoms. A total of 600 specimens were analysed. Results: Non-neoplastic lesions were more common than neoplastic lesions (570 out of 600). Lesions were more common in 2nd to 5th decades with male preponderance. Among nonneoplastic lesions, majority of non-neoplastic lesion were of appendiceal lesion (247) followed by non-specific inflammation (138). Out of 30 neoplastic lesions; most common were of adenocarcinoma (15 cases). Conclusion: A wide variety of neoplastic and non-neoplastic lesions were diagnosed in the present study. In small intestine, non-neoplastic lesions were common while most of the malignant lesions were common in large intestine. The most common non-neoplastic lesion was appendicitis followed by non-specific inflammation and the most common neoplastic lesion was adenocarcinoma.